Twelve tips for running successful junior doctor-led teaching programmes for medical students. (28th March 2013) - Mabvuure, Nigel Tapiwa; Rodrigues, Jeremy; Cumberworth, Alex; Mahmud, Mohammad
Abstract : Background: Medical students value teaching by junior doctors and find it comparable to consultant-led teaching. Although several junior doctor-led teaching programmes have been developed, there is insufficient information in the literature to guide junior doctors planning on developing such programmes. Aim: This article gives junior doctors 12 practical tips on how they might develop and run successful teaching programmes for medical students. Results: The 12 tips are (1) Clearly define the scope of your programme, (2) Ensure student-defined learning goals are included at an early stage, (3) Inform and involve your fellow junior doctors in teaching, (4) Plan teaching rotas in advance, (5) Learn to teach effectively by attending courses, (6) Promote your programme to medical students as widely as possible, (7) Use varied and interactive teaching methods, (8) Establish rapport with students, (9) Include assessment as part of the teaching programme, (10) Seek feedback from attendees and senior faculty, (11) Establish rules for tutorials and (12) Secure formal recognition for your scheme. Conclusions: These 12 tips may help junior doctors to develop and manage successful teaching programmes. It may also be a useful guide for senior faculty advising junior doctors who aspire to establish such teaching programmes.